The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/w13020215
|View full text |Cite
|
Sign up to set email alerts
|

Current and Emerging Adsorbent Technologies for Wastewater Treatment: Trends, Limitations, and Environmental Implications

Abstract: Wastewater generation and treatment is an ever-increasing concern in the current century due to increased urbanization and industrialization. To tackle the situation of increasing environmental hazards, numerous wastewater treatment approaches are used—i.e., physical, chemical, and biological (primary to tertiary treatment) methods. Various treatment techniques being used have the risks of producing secondary pollutants. The most promising technique is the use of different materials as adsorbents that have a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(72 citation statements)
references
References 198 publications
(177 reference statements)
0
52
0
4
Order By: Relevance
“…The scarcity of irrigation water compels farmers to use untreated wastewater and industrial effluents for crop production particularly in developing countries [7,51]. While it is known that wastewater increases crop production due to dissolved nutrients and beneficial impacts on soil properties, it is also a source of heavy metals in soils and growing crops [9,52]. Heavy metals are potentially toxic for plants, animals, and human beings due to their non-biodegradable nature [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of irrigation water compels farmers to use untreated wastewater and industrial effluents for crop production particularly in developing countries [7,51]. While it is known that wastewater increases crop production due to dissolved nutrients and beneficial impacts on soil properties, it is also a source of heavy metals in soils and growing crops [9,52]. Heavy metals are potentially toxic for plants, animals, and human beings due to their non-biodegradable nature [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Lignin and cellulose have as primary components –OH and –COOH functional groups that can substitute the H + with As(III), Cd(II), Cr(IV), Hg(II), Pb(II), and Ni(II) as metalloids and metal ions in order to generate complexes, as it was tested for grape and apple wastes, grounds from tea and coffee, nutshells, leaves, algae, rice, and sunflower plants [ 41 ]. In order to enhance the adsorption capacity and reinforce the functional groups potential of these agricultural waste-derived adsorbents, their structure can be modified by different physical and chemical pre-treatments, obtaining carbonaceous materials (biochar), with high surface area and pore volume [ 42 , 43 ].…”
Section: Agri-food Waste Quantificationmentioning
confidence: 99%
“…According to Younas et al, there is a real challenge regarding the treatment methods of wastewaters in correlation with the pollutant sources [ 41 ]. The authors identified two main sources, natural and derived from anthropogenic activities, emphasizing the generation sources for those pollutants that seriously affect the environment and health.…”
Section: Types Of Pollutantsmentioning
confidence: 99%
See 2 more Smart Citations